Recommendations for the primary prevention of atherosclerotic cardiovascular disease in primary care: a systematic guideline review - Maren Bredehorst; Ana I. González-González; Lara Schürmann; Dennis Firmansyah; Christiane Muth; Jörg Haasenritter; Veronika van der Wardt; Svetlana Puzhko (Frontiers in Medicine)
IntroductionThis study systematically reviews and synthesizes recommendations from national and international clinical practice guidelines (CPGs) regarding the primary prevention of atherosclerotic cardiovascular disease (ASCVD) in adults in primary care settings.MethodsCPGs were retrieved from MEDLINE, Trip, guideline repositories, and websites of guidelines-producing societies. Two reviewers independently screened the guidelines for eligibility, assessed their quality, and extracted study characteristics and relevant recommendations for further consistency analysis. Recommendations, with their strength and evidence level, were thematically coded and clustered around clinical questions using ATLAS.ti.ResultsWe included 26 CPGs from which we extracted 581 recommendations on risk assessment, non-pharmacological, and pharmacological interventions. Twenty-one guidelines (81%) were rated as having “very good” methodological quality. We categorized the recommendations into 124 clusters. Forty-four clusters (35%) included consistent recommendations, but only four of them (3%) included highly consistent recommendations. These clusters emphasized avoiding routine prescriptions of nicotinic acid, aspirin, and fibrates for primary ASCVD prevention alone, and recommending 20 mg/day of atorvastatin for high-risk ASCVD patients. The recommendations also highlighted the importance of adhering to a Mediterranean-type diet, patient-centered counseling, and standardized risk assessment for patients over the age of 40.DiscussionThis review underscores the heterogeneity in primary ASCVD prevention recommendations and the importance of personalized strategies for at-risk individuals.Systematic review registrationPROSPERO, CRD42023394605, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023394605.